THE DEVELOPMENT OF INTERACTIVE MODULE TO SUPPORT STUDENT CENTERED LEARNING - Sudarman Sudarman; Ardian Ardian (Akademika, 2021)
This study aims to develop an interactive module that supports student-centered learning and test the feasibility and the response of students to the interactive module. The product development stages use the Analyze, Design, Development, Implementation, and Evaluation procedure. The validation of the developed products was carried out by two material experts and two media experts. Products that have been revised and get a proper assessment are tested out in small groups consisting of 5 teachers and tested in large groups consisting of 30 students. The results show that the interactive module as a support for Student Centered Learning is very good and feasible to use. This is based on the results of the validation of material experts which show the percentage of the feasibility level of 95% and the results of the validation of the media experts show the percentage of the feasibility level of 80%, while the small group trials and large group trials show the percentage of the feasibility level of 87% and 86% respectively. Meaning that it is in the very feasible category.